2013
DOI: 10.1371/journal.pgen.1003767
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and Rapid Transfer-RNA Deactivation as a Mechanism of Translational Repression in Stress

Abstract: Stress-induced changes of gene expression are crucial for survival of eukaryotic cells. Regulation at the level of translation provides the necessary plasticity for immediate changes of cellular activities and protein levels. In this study, we demonstrate that exposure to oxidative stress results in a quick repression of translation by deactivation of the aminoacyl-ends of all transfer-RNA (tRNA). An oxidative-stress activated nuclease, angiogenin, cleaves first within the conserved single-stranded 3′-CCA term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
106
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(132 citation statements)
references
References 42 publications
19
106
1
2
Order By: Relevance
“…This is in contrast to our findings here that both 5= and 3= tiRNAs are selectively enriched in the novel Cyt c-RNP complex. More recently, it was shown that oxidative stress induced by arsenite treatment of HeLa cells inhibited translation elongation concomitant with ANG-mediated cleavage of the aminoacyl-ends of all tRNAs (45). This observation may explain the decreased association of Cyt c with full-length tRNAs during ANG treatment (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…This is in contrast to our findings here that both 5= and 3= tiRNAs are selectively enriched in the novel Cyt c-RNP complex. More recently, it was shown that oxidative stress induced by arsenite treatment of HeLa cells inhibited translation elongation concomitant with ANG-mediated cleavage of the aminoacyl-ends of all tRNAs (45). This observation may explain the decreased association of Cyt c with full-length tRNAs during ANG treatment (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…18 In addition, ANG cleaves the conserved singlestranded 39-CCA termini of all tRNAs, thereby promoting the deactivation of the aminoacyl-ends of tRNA and subsequently inhibiting translation. 43 Therefore, ANG participates in translation attenuation in ER-stressed cells through an original process of RNA interference which therefore expands UPR-induced mechanisms for the reduction of protein flux into the ER and comes in addition to the previously described phosphorylation of eIF2a, 44 regulated IRE1a-dependent decay of RNAs, 36 and selective mRNA release from the ER. 45 Our data also indicate that in the first hours after ER stress induction, ANG-mediated translation repression correlates with ANG dissociation from the ANG-inhibitor RNH1.…”
Section: Discussionmentioning
confidence: 98%
“…9 CCA-adding enzymes are also implicated in tRNA quality control and the stress response. [10][11][12][13] TRNT1 encodes the only human CCA-adding activity and is responsible for the maturation of both cytosolic and mitochondrial tRNAs. 11 siRNA knockdown of TRNT1 in wild-type human fibroblasts caused cytotoxicity and apoptosis (supplemental Figure 3), suggesting that eliminating TRNT1 function altogether is lethal, whereas mutations only impairing function could be disease-associated.…”
mentioning
confidence: 99%